Esquizoanálise e cartografias no pensamento jusfilosófico: percursos do logos ao nomos - Patto, Belmiro Jorge (2014)
This thesis, from schizoanalysis, their assemblages with the philosophy of difference or nomadic thought, calls into question the viability of the thought of the concept of Law as contributed by the philosophy of representation, since Plato, from the dogmatic image of thought, to contemporary legal theories, imprison such a concept in the idea of justice as fair measure , and as logical operators have the common sense and good judgment. From the point of view defended here, thought as differential of Idea, makes this concept impossible and attests to the need of creating another concept from another image of thought. It is necessary then, the destruction of categories such as society, State and subject because in addition to its centrality to the dogmatic thinking, show up already traversed by aporias and paradoxes that ultimately lead to deadlocks which today are evident, such as representative democracy, human rights, just wars, capitalism as an economic theory, since cause the Law its despotenciation and sterility, even as instrument of justice . Hence the quest for another method, cartographies, which gives an account of the complications, implications, explications and perplications in Idea, which takes the thinking to its relations with outside, the becoming and desire. It s in the lines of flight s itinerancy that, in problematic encounters of ways of precarious existences produces socialities, radiate the numismatic flows of force relations of Power, and establishes the nomadic war machine as you can manage other dynamics space/time and builds the plane of immanence that will be populated by artisans of such lines of flight that bear witness the jurisprudence as ethics able to release the powers of thought from his dogmatic imprisonment, towards experimentation, improvisation, compositions that increase or decrease in our affections, in encouters and events . Without the prospect of purposes, from this point of view one reaches to the should be, as random throw of the dice